MISDIAGNOSED OF NASOPHARYNGEAL CARCINOMA - Martina Marthatilova; Nani Iriani Djufri (TALENTA PUBLISHER, 2020)
Introduction : Nasopharyngeal carcinoma is the most common head and neck malignancy in Indonesia. Diagnosis errors often occur in nasopharyngeal carcinoma due to non-specific symptoms such as symptoms of an infectious disease that resemble the symptoms of nasopharyngeal carcinoma. Case Report : In this case, it was explained how this diagnostic error occurred. A man, 39 years old with complaints of right and left neck lumps, the patient initially came to an ear nose throat (ENT) specialist and performed fine needle aspiration (FNA) and suggested a biopsy. But the patient did not continue his treatment at an ENT doctor. The patient continued his treatment at pulmonologist and was diagnosed with glandular Tuberculosis (TB) and received TB treatment. In the following 4th month on TB therapy, a lump in the right and left neck was felt getting bigger, then the pulmonary expert refers the patient to the oncology surgeon, the oncology surgeon department then refers to the ENT specialist because of the suspicion towards nasopharyngeal carcinoma. In the ENT department biopsy is performed on the nasopharynx and the result is bilateral nasopharyngeal Non-Keratinizing Cell Carcinoma, undifferentiated (WHO type III). Conclusion: The patient was diagnosed with stage IV B nasopharyngeal carcinoma (T1N3M0). Currently, the patient has undergone chemotherapy with the paclitaxel and cisplatin regimen, and the 3rd cycle chemotherapy has been done.